The future of collective bargaining in the South African public sector employment relationship - Madiba, Clive (My University, 2024)
Refer to document
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2024
Keywords: Collective bargaining; South African Public Sector; Employment relationships; Collective bargaining; Employee rights; Public service employment -- Law and legislation -- South Africa; Public service employment -- South Africa